2022
DOI: 10.3390/bioengineering9060235
|View full text |Cite
|
Sign up to set email alerts
|

A New Mathematical Numerical Model to Evaluate the Risk of Thrombosis in Three Clinical Ventricular Assist Devices

Abstract: (1) Background: Thrombosis is the main complication in patients supported with ventricular assist devices (VAD). Models that accurately predict the risk of thrombus formation in VADs are still lacking. When VADs are clinically assisted, their complex geometric configuration and high rotating speed inevitably generate complex flow fields and high shear stress. These non-physiological factors can damage blood cells and proteins, release coagulant factors and trigger thrombosis. In this study, a more accurate mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…69 However, it has been shown in other studies that steady methods are adequate for analyzing continuous flow blood pumps. 19,68 The results obtained from the steady simulations in this study are in high agreement with experiments (Figure 3) and also prove the reliability of the steady method. Second, most of the conclusions of this study were obtained by simulations and required to be confirmed experimentally.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…69 However, it has been shown in other studies that steady methods are adequate for analyzing continuous flow blood pumps. 19,68 The results obtained from the steady simulations in this study are in high agreement with experiments (Figure 3) and also prove the reliability of the steady method. Second, most of the conclusions of this study were obtained by simulations and required to be confirmed experimentally.…”
Section: Discussionsupporting
confidence: 84%
“…In some studies, it is believed that the RANS simulation cannot capture dynamic changes between the impeller and tongue 69 . However, it has been shown in other studies that steady methods are adequate for analyzing continuous flow blood pumps 19,68 . The results obtained from the steady simulations in this study are in high agreement with experiments (Figure 3) and also prove the reliability of the steady method.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations